Acquirers and financial constraints: Theory and evidence from emerging markets - Rahul Mukherjee; Christian Proebsting (Graduate Institute of International and Development Studies, 2017)
How do financial frictions shape the set of acquirers, how much they acquire, and how long they keep ownership? To address these questions, we develop a tractable model of M&As whereby acquirers and targets emerge endogenously due to differences in liquidity. Financial crises lead to selection effects among acquirers that result in larger acquired stakes and more persistent ownership. We present evidence consistent with the predictions of the model in a dataset of domestic and cross-border M&As from emerging markets. Financially constrained domestic firms in crisis-hit countries acquire 11-15% more ownership. The survival rate of these acquisitions is 19-24% higher.
Keywords: F21; G01; G34; 330; domestic mergers and acquisitions; cross-border mergers and acquisitions; financial crisis; financial constraints; capital reallocation